2009
DOI: 10.1002/lary.20533
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of human papillomavirus in oropharyngeal squamous cell carcinomas

Abstract: In patients with oropharyngeal carcinoma uniformly treated with chemoradiation, the presence of HPV is a favorable prognostic indicator with respect to recurrence and overall survival. However, advanced T stage was an independent risk factor for recurrence and death that can to some degree offset this benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
5
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 25 publications
8
91
5
3
Order By: Relevance
“…Therefore, it can be speculated that different epigenetic and genetic pathways may affect cancer evolution and prognosis. Although we are only just starting to understand the impact of molecular findings in patient prognosis, previous reports have already suggested that HPV infection has an impact on the prognosis of HNSCC (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be speculated that different epigenetic and genetic pathways may affect cancer evolution and prognosis. Although we are only just starting to understand the impact of molecular findings in patient prognosis, previous reports have already suggested that HPV infection has an impact on the prognosis of HNSCC (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…However, this strong positive prognostic factor is often confirmed in tonsillar and oropharyngeal carcinomas. Notably, the majority of studies that demonstrated increased survival were reporting on patients with oropharyngeal and/or tonsillar tumors Lindel et al, 2001;Sedaghat et al, 2009). The meta-analysis by Ragin et al examining the relationship between HPV and overall survival did not show any survival differences between HPV-positive and HPVnegative patients with cancer in non-oropharyngeal sites .…”
Section: Prognosis Of Hpv Positive Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…However, this strong positive prognostic factor is often confirmed in tonsillar and oropharyngeal carcinomas. Notably, the majority of studies that demonstrated increased survival were reporting on patients with oropharyngeal and/or tonsillar tumors (Ang et al, 2010;Lindel et al, 2001;Sedaghat et al, 2009). The meta-analysis by Ragin et al examining the relationship between HPV and overall survival did not show any survival differences between HPV-positive and HPVnegative patients with cancer in non-oropharyngeal sites .…”
Section: Prognosis Of Hpv Positive Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%